Quick Reference Guide to Foliar Fungicides - Megan M. Dewdney (EDIS)
This reference guide provides quick access to foliar fungicide recommendations from the Florida Citrus Production Guide. Also included are guidelines for fungicide resistance management. This 2-page publication is a minor revision written by Megan M. Dewdney and published by the Plant Pathology Department, August 2018.